Improvement of maize drought tolerance by foliar application of zinc selenide quantum dots - Kanna, Venkatesan Kishanth; Djanaguiraman, Maduraimuthu; Senthil, Alagarswamy; Moorthy, Ponnuraj Sathya; Iyanar, Krishnamoorthy; Veerappan, Anbazhagan (Frontiers in Plant Science, 2024)
Maize (Zea mays L.) is an important cereal crop grown in arid and semiarid regions of the world.During the reproductive phase, it is more frequently exposed to drought stress, resulting in lower grain yield due to oxidative damage. Selenium and zinc oxide nanoparticles possess inherent antioxidant properties that can alleviate drought-induced oxidative stress by catalytic scavenging of reactive oxygen species, thereby protecting maize photosynthesis and grain yield. However, the effect of zincselenide quantum dots (ZnSe QDs) under drought stress was not quantified earlier. Hence, the aim of the study was to quantify the (i) toxicity potential of ZnSe QDs and (ii) drought mitigation potential of ZnSe QDs by assessing the transpiration rate, photosynthetic rate, oxidants production, antioxidant enzyme activity and seed yield of maize under limited soil moisture levels. Toxicity experiments were carried out with 0 to 500 mg L -1 of ZnSe QDs on earthworms and azolla, and the result showed that up to 20 mg L -1 , the growth rates of earthworm and azolla were not affected. Dry down experiment was conducted with three treatments, namely foliar spray of (i) water, (ii) ZnSe QDs (20 mg L -1 ), and (iii) combined zinc sulphate (10 mg L -1 ) and sodium selenate (10 mg L -1 ). ZnSe or Se applications under drying soil reduced the transpiration rate compared to water spray by partially closing the stomata.ZnSe application at 20 mg L -1 at the tasselling stage significantly increased the photosynthetic rate (25%) through increased catalase (98%) and peroxidase (85%) enzyme activity and decreased the hydrogen peroxide (23%) content than water spray, indicating premature leaf senescence was delayed under rainfed condition. ZnSe spray increased seed yield (26%) over water spray by an increased number of seeds m -2 (42%). The study concluded that ZnSe (20 mg L -1 ) foliar application could 34 decrease the drought-induced effects in maize. 35